THE CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI HINDU 2 SUKAWATI IN ACADEMIC YEAR 2021/2022 - Paulina Romario; Ida Ayu Made Sri Widiastuti (Academic Journal on English Studies (AJOES), 2022)
The objective of this study was to find out the significant correlation between grammar mastery and writing achievement of the eighth-grade students of SMP Negeri Hindu 2 Sukawati in the academic year 2021/2022. The design was a correlation study research design. The sample was 40 students. In collecting the data for this research, the writer used two types of tests: the grammar mastery test to test students' grammar mastery of past tense and the writing test to recount paragraphs for testing students' writing achievements. It got a score of 3.010 for grammar mastery and 3.232 for writing achievement. The data were analysed by using SPSS 25.0 which consists of the Normality test, Homogeneity test, Pearson Product Moment, and T-testing. The finding out of the study revealed that the hypothesis in this study was high correlation accepted. According to the result of Pearson Product Moment, it is found that r was 0.608. It lies between 0.600 – 0.800 which is a high level. Based on the result, it can be concluded that there is a significant correlation between grammar mastery and writing achievement of the eighth-grade students of SMP Negeri Hindu 2 Sukawati in the academic year 2021/2022.